Planejamento e Gestão Universitária na UFCG: uma análise crítica do Plano de Desenvolvimento Institucional – 2010 a 2014 - Patrício Neto, Honório (2017)
This work presents a critical analysis of the planning carried out by the Federal University of Campina Grande (UFCG). The Institutional Development Plan (PDI) presents itself as the main piece of planning for a higher education institution. Thus the following questions arise: How has the Federal University elaborated its institutional development plan? What contribution can be made by the educational management theory and educational planning for the UFCG PDI? Can the use of accounting information and management and budget accounting techniques collaborate in the demonstration of financial sustainability of the PDI? The methodology used chose a hermeneutic approach with qualitative and quantitative research using the following techniques: bibliographic research, participant observation, and, mainly, the analysis of documents. The results obtained were the identification of the two most relevant problems: the planning actions of the Federal University of Campina Grande require greater participation of the university community and the lack of articulation between the institutional development plan and the budgetary execution of the Federal University of Campina Grande. At the end, a script is presented to assist in the preparation of the UFCG Institutional Development Plan.